Relationship between Working period and Personal Hygiene towards the Incidence of ARI Among Fish Fillet Workers (Case Study In TPI Tegal City 2017) (Universitas Negeri Semarang, 2018)
The International Labor Organization's (ILO) world body says the third cause of death from work is a respiratory disease. Working periods are important to seeÂ how long a person has been exposed to unhealthy environments or chemicals. The longer a person works on the unhealthy the higher the risk of health problems. While the problem of Personal Hygiene is a daily thing to do, but sometimes still considered less important. The purpose of this study is to analyze the working period and personal hygiene of ARI cases among fish fillet workers in TPI Tegal City. This research is a kind of quantitative research. Analytical observational research design with case control approach.The population of all Fish Fillet workers in TPI Tegal City and sample of 80 samples was obtained by lameshow formula. With a sample of 40 samples and a control sample of 40 samples. The sample was obtained by the technique of Consecutive Sampling Instrument used was questionnaire. Data analysis using Chi square test. The result of the research showed that there was a significant correlation between work period to ARI occurrence among fish fillet workers in TPI Tegal City (p = 0,000) with OR = 10,55 and no significant relationship between personal hygiene to ARI occurrence among fillet workers fish in TPI Tegal City (p = 0,189). The conclusion of long-time fish fillet workers (â‰¥ 5 years) is 10 times greater risk of ARI than new workers (5 years) working as fish fillet workers in TPI Tegal City.